The geopolitics in plan Colombia - Petras, James (La Sociología en sus Escenarios, 2009)
Abstract. The Plan Colombia is an U.S. multi-track policy of military confrontation between the state apparatus and paramilitary forces in Colombia. It is based on diplomatic and political pressure like elites in civil society in Venezuela; or political-economic co-optation of the Ecuadorean executive. Resumen. El Plan Colombia es una política multilateral de confrontación militar de EE.UU, entre aparatos del Estado y las fuerzas paramilitares en Colombia. Se basa en la presión política y diplomática como la aplicada a las élites de la sociedad civil en Venezuela, o política y económicamente: la cooptación del ejecutivo ecuatoriano.